A pilot randomized controlled double-blind trial of intermittent theta burst stimulation (iTBS) repetitive transcranial magnetic stimulation (rTMS) to improve memory in mild cognitive impairment (MCI): a study protocol - Maria I. Lapid; Sandeep R. Pagali; Michael R. Basso; Paul E. Croarkin; Jennifer R. Geske; John Huston; Karimul Islam; Boney Joseph; Walter W. Kennebeck; Daehun Kang; Simon Kung; Allison M. LeMahieu; et al. (Pilot and Feasibility Studies)
Abstract Background Mild cognitive impairment (MCI), prevalent among older adults, often precedes Alzheimer’s disease (AD) or Alzheimer’s disease-related dementias (ADRD), emphasizing the need for effective interventions. Early intervention in MCI is crucial, not only to alleviate symptoms but to potentially delay the progression of cognitive decline. The lack of definitive treatments for MCI has prompted the exploration into alternative non-pharmacological therapeutic approaches. Specifically, noninvasive brain stimulation using repetitive transcranial magnetic stimulation (rTMS) has demonstrated promise in improving cognition in MCI and AD. Objectives Our study will test the feasibility of using intermittent theta burst stimulation (iTBS) technique of rTMS in MCI, pilot test the study design, and collect pilot data on the effect of iTBS over three different brain regions on working memory, new learning, and executive function in MCI. Exploratory objectives are to assess the feasibility and usefulness of functional magnetic resonance imaging (fMRI), high-density electroencephalography (HD-EEG), and sleep architecture as potential biomarkers in response to iTBS. Methods A pilot randomized double-blind controlled cross-over trial of iTBS on 20 MCI participants randomized to 10 days of active iTBS (left dorsolateral prefrontal cortex or left lateral parietal cortex) or control (vertex). After 4–6-week washout period, they cross over to the alternative treatment arm for another 10 days. Each participant will undergo a total of 20 iTBS sessions. Pre- and post-iTBS assessments include neuropsychological tests, fMRI, HD-EEG, and sleep architecture. Discussion This innovative study aims to test the feasibility of iTBS as a cognitive enhancement strategy in MCI. If our study is feasible, it could lead to a future larger trial to further test whether iTBS can modulate underlying neurobiology and offer a therapeutic avenue to remediate cognitive decline in MCI or ultimately delay progression to dementia. Trial registration ClinicalTrials.gov, NCT05327257. Registered 04 April 2022.